Capacitive Energy Storage (CES) Optimization For Load Frequency Control in Micro Hydro Power Plant Using Imperialist Competitive Algorithm (ICA) - Djalal, Muhammad Ruswandi; Yunus, Muhammad; Imran, Andi; Setiadi, Herlambang (Politeknik Elektronika Negeri Surabaya (PENS), 2017)
This research will discuss a strategy of frequency control at micro hydro power plant using Capacitive Energy Storage (CES). CES is a device that can store and release energy quickly. To optimize CES performance, proper tuning is required to optimize CES performance. To obtain optimal CES parameter on micro hydro, artificial intelligence method based on Imperialist Competitive Algorithm (ICA) is used. Proportional Integral Derivative Controller (PID) is still a controller that can not be separated from the system, therefore in this research will be combined with CES as the main controller for frequency control on micro hydro. The simulation results show that the application of ICA in optimizing PID-CES parameters, can well improve micro hydro performance. The control models discussed in this research are Proportional Controller (P), Proportional Integral Controller (PI), Proportional Derivative Controller (PD), PID Controller, CES Controller and PID-CES Controller. From the simulation results obtained, P controller overshoot of -0.0001254, with PI Controller -0.000125, with PD Controller -0.0001252, with PID controller -0.0001249, with CES controller -0.0001224, and with PID-CES -1.371e-05. From the results of some of the controller models, it can be concluded that the PID-CES controller proposed in this study has a very significant effect to reduce the frequency oscillation in micro hydro, and it is very suitable to be applied for frequency control at micro hydro.